Extraction of Potassium from Biotite by Lithium Ion Exchange and Its Electrochemical Properties. (November 2019) - Cheng, Yilin; Huang, Zhiliang; Yao, Donghui; Wu, Changsheng
Abstract: In order to solve the problem of shortage of potassium resources in China, the technology of extracting soluble potassium from insoluble potassium minerals needs to be further studied. Biotite with relatively high potassium content was used as the research object to extract soluble potassium elements from biotite by lithium ion exchange method, and the electrochemical properties of biotite were tested after potassium extraction. After 80°C hydrothermal reaction for hours, potassium and lithium ion exchanged with each other, and soluble potassium were obtained from the filtrate by filtering the reaction liquid. The efficiency of potassium extraction and the structure of mica changed after the oxidation reaction was determined by XRF and XRD, respectively. The results showed that the layered silicate structure of mica after the reaction was not destroyed, and the potassium extraction rate for 8h was up to 92.3%. The discharge capacitance was 1.32F/g, and the coulomb efficiency was 64% in 0.6C.